Access to the Bis‐benzene Cobalt(I) Sandwich Cation and its Derivatives: Synthons for a "Naked" Cobalt(I) Source?. Issue 30 (25th June 2018) - Meier, Stefan C.; Holz, Albina; Kulenkampff, Jan; Schmidt, Alexei; Kratzert, Daniel; Himmel, Daniel; Schmitz, Dominik; Scheidt, Ernst‐Wilhelm; Scherer, Wolfgang; Bülow, Christine; Timm, Martin; Lindblad, Rebecka; et al.
Abstract: The synthesis and structural characterization of the hitherto unknown parent Co(bz)2 + (bz=benzene) complex and several of its derivatives are described. Their synthesis starts either from a CoCO5 + salt, or directly from Co2 (CO)8 and a Ag + salt. Stability and solubility of these complexes was achieved by using the weakly coordinating anions (WCAs) [Al(OR F )4 ] − and [FAl(OR F )3 2 ] − R F =C(CF3 )3 and the solvent ortho ‐difluorobenzene ( o ‐DFB). The magnetic properties of Co(bz)2 + were measured and compared in the condensed and gas phases. The weakly bound Co( o ‐dfb)2 + salts are of particular interest for the preparation of further Co I salts, for example, the structurally characterized low‐coordinate 12 valence electron Co(P t Bu3 )2 + and Co(NHC)2 + salts. Abstract : Synthons for a "naked" Co + source : A salt of the long‐sought triplet state Co(C6 H6 )2 + complex and some derivatives are described. The magnetic properties in condensed phases are compared to the gas phase measurement. The "naked" Co(difluorobenzene)2 + salts are potent materials for ligand exchange reactions leading to, for example, two‐coordinate Co(P t Bu3 )2 + .